Metachronous primary cancer of the tongue and malignant lymphoma of the small intestine: A case report. Issue 7 (19th February 2021) - Sugimoto, Keisuke; Uejima, Shinji; Uchiyama, Yumiko; Yasue, Reita; Nambu, Kazuya; Ishikawa, Jun; Koma, Yoshiro; Akita, Takako; Toh, Taketomo; Fujimoto, Takehiro
Abstract: Rationale: Oral cancer often causes secondary primary cancers in the upper gastrointestinal tract. However, there are no reports of secondary primary cancers in patients with oral squamous cell carcinoma and malignant lymphoma of the small intestine. This report describes a case of metachronous multiple primary cancers of the tongue and small intestine malignant lymphoma. Patients concerns: The patient was admitted to our department with the chief complaint of pain in the right tongue. Partial tongue resection and supraomohyoid neck dissection were performed. One year after surgery, the patient experienced abdominal pain and bloody stools. Diagnosis: Diffuse large B-cell lymphoma (DLBCL) was diagnosed via histological examination. Interventions: A terminal ileum resection was performed. Postoperatively, the patient received 6 courses of rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine, and prednisone (R-CHOP). Outcomes: Five years after his initial diagnosis, there is no evidence of recurrence, metastasis, or other primary cancer. Lessons: Oral cancer patients should always be followed up owing to a possibility of malignant tumors in other areas.